Methane reforming over a high temperature stable-NiCoMgOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Chemical Engineering Journal, 2006)
The unusually high temperature stable NiCoMgOx (Ni/Co/Mg: 1:0.2:1.2)/zirconia-hafnia catalyst has been investigated for syngas generation via the catalytic partial oxidation of methane (CPOM), oxidative steam reforming of methane (OSRM) and oxidative CO2 reforming of methane (OCRM) processes. The catalyst, even when calcined at 1400 degrees C for 4 h, showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions. On account of its high thermal stability, hot spots in the catalyst bed and/or high temperatures prevailing at the catalyst surface during the oxy-reforming processes would have little or no effect on the catalytic activity/selectivity of the NiCoMgOx/zirconia-hafnia catalyst, thus making the catalyst suitable even for operating under adiabatic conditions. While the selectivity for CO increased considerably with increasing reaction temperature for the CPOM process, the selectivity for H-2 was affected to a much lesser extent. The selectivity for CO and H-2 in the CPOM reaction was found to decrease with increasing space velocity; the H-2 selectivity was however affected to a greater extent. For the OSRM process, the H2O/CH4 ratio profoundly influenced the H-2/CO ratio and the heat of the reaction. Depending on the H2O/CH4 ratio, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion increased rapidly with increasing OCRM temperature and correspondingly the exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. At 900 degrees C, the OCRM reaction was mildly exothermic and provided high methane conversion and syngas selectivity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: high temperature stable catalyst; methane; oxy-dry reforming; oxy-steam reforming; Partial oxidation

Partial oxidation of methane to syngas with or without simultaneous steam or CO2 reforming over a high-temperature stable-NiCoMgCeOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
A NiCoMgCeOx (Ni/Co/Mg/Ce: 1:0.2:1.2:1.2)/zirconia-hafnia catalyst with unusually high thermal stability has been investigated for syngas generation via a process that includes the catalytic partial oxidation of methane (CPOM), the oxidative steam reforming of methane (OSRM) and the oxidative CO2 reforming of methane (OCRM). The catalyst calcined at 1400 degrees C (for 4 h) showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions; furthermore no catalyst deactivation was observed for a period of 20 h. For the CPOM process, the selectivity for H-2 was > 95% at reaction temperatures > 650 degrees C however temperatures above 800 degrees C were required to achieve > 95% CO selectivity. While the reaction temperature had a considerable influence on the CPOM product H-2/CO ratio, the space velocity (at 850 degrees C) did not affect it to any significant extent. For the OSRM process, the H2O/CH4 ratio and the reaction temperature had a strong effect on the product H-2/CO ratio and the heat of the reaction; depending on the H2O/CH4 ratio and reaction temperature, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion was very strongly affected by the reaction temperature in the OCRM process; reasonably high CO2 conversion ( > 40%) could only be obtained at high OCRM reaction temperatures ( > 850 degrees C). The exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry (CO2) reforming; high-temperature stable; methane; oxy-steam reforming; Partial oxidation; Steam reforming; Syngas

Oxy-methane reforming over high temperature stable NiCoMgCeOx and NiCoMgOx supported on zirconia-haffnia catalysts: accelerated sulfur deactivation and regeneration - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Catalysis Communications, 2007)
NiCoMgOx and NiCoMgCeOx on commercial low surface area zirconia-haffnia catalysts have unusually high thermal stability (>= 2000 degrees C) for syngas generation via the methane partial oxidation process (J. Catal., 233, 36, 2005). Herein we report the results on accelerated sulfur deactivation (0.74 mol% sulfur in feed) and corresponding regeneration (at 800 degrees C in 1:1 O-2 + N-2 flow) over these catalysts. The NiCoMgCeOx catalyst, due to a larger mobility of lattice oxygen, showed a considerably higher resistance to sulfur poisoning; the higher mobility of the lattice oxygen in case of the NiCoMgCeOx catalyst may be related to the presence of CeO2. During the deactivation process, the selectivity for H-2 was decreased to a much greater extent than that for CO. Regeneration studies showed that even after complete deactivation of the catalysts, the original activity/selectivity of both the catalysts could be completely restored after a simple regeneration process. Based on their exceptionally high thermal stability, high activity/selectivity and easily regenerability, the NiCoMOx, and NiCoMgCeOx catalysts appear to be very promising candidates for the CPOM process. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Deactivation; high temperature stable; methane; Partial oxidation; Regeneration; Sulfur

Energy-efficient syngas production through, catalytic oxy-methane reforming reactions - Choudhary, Tushar V.; Choudhary, Vasant R. (Angewandte Chemie-International Edition, 2008)
Keywords: fuels; heterogeneous catalysis; methane activation; Partial oxidation; Syngas

Solvent-free selective oxidation of benzyl alcohol to benzaldehyde by tert-butyl hydroperoxide over U3O8-supported nano-gold catalysts - Choudhary, Vasant R.; Dumbre, Deepa K. (Applied Catalysis A-General, 2010)
Liquid-phase oxidation of benzyl alcohol to benzaldehyde by tertiary butyl hydroperoxide over different uranium oxide supported nano-gold catalysts in the absence of a solvent has been thoroughly investigated. The influences of catalyst parameters [viz, method of gold deposition (impregnation, co-precipitation, deposition-precipitation and homogeneous deposition-precipitation), gold loading (08 wt%) and catalyst calcination temperature (100-900 degrees C)] on the catalyst performance have been investigated. The influence of reaction conditions [viz, reaction time (0-2 h) and temperature (25-94 degrees C)] on the process performance has also been studied. The Au/U3O8 catalyst prepared by the homogeneous deposition-precipitation and calcined at 400 degrees C showed very high activity (100% benzyl alcohol conversion with >85% selectivity for benzaldehyde) in the process for a short reaction period (0.5 h) at 94 degrees C. The catalyst also showed excellent reusability in the process. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Au/U3O8 catalyst; Benzaldehyde; Benzyl alcohol; Nano-gold; Partial oxidation; tert-Butyl hydroperoxide